Comparison between mixtures of asphalt with Palm Oil Shells and coconut Shells as additives - Al-Mansob, Ramez A.; Amiruddin Ismail,; A. Algorafi, Mohammed; Hafezi, Mohammad Hesam; Baghini, Mojtaba Shojaei (Fakulti Kejuruteraan ,UKM,Bangi., 2013)
The finding of other alternative material that has become the concern of various works lies in the fact that the material is to serve as an additive in asphalt mixes to enhance its physical properties. This paper deals with a laboratory study which compares the performance of hot mix asphalt (HMA) with the use of palm oil shells (POS), also with coconut shells (CS) as an additive and control samples. Both the palm oil shells and coconut shells are put in separately, taking up the shape of coarse aggregate with the size of 4.75 mm. The amount of these palm oil shells and coconut shells blended into the mixes is expressed in respective percentage (0,5, 10, 15 and 20%) of the total weight of the size 4.75 mm of aggregate. The Superpave method was employed to design the mixes. Samples were prepared and put to the test for the rutting characteristic as the indicator to the performance examined. It was observed that the addition of the coconut shells has made the HMA better with respect to their resilient modulus under 40˚C of temperature, it is cleared that 20% of CS as additive is the best percentage in term of resilient modulus among the percentages that have been chosen. However, it is contrary for the POS. The POS and CS addition will lead to that the asphalt concrete becoming more responsive to permanent deformation (static and dynamic creep) for more than 5% of shells content. In general, the CS emerges as better additives than POS in the HMA.